2018
DOI: 10.1002/jssc.201701206
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide‐based chiral stationary phases as halogen bond acceptors: A novel strategy for detection of stereoselective σ‐hole bonds in solution

Abstract: In the last few years, halogen bonds have been exploited in a variety of research areas both in the solid state and in solution. Nevertheless, several factors make formation and detection of halogen bonds in solution challenging. Moreover, to date, few chiral molecules containing electrophilic halogens as recognition sites have been reported. Recently, we described the first series of halogen-bond-driven enantioseparations performed on cellulose tris(3,5-dimethylphenylcarbamate) by high-performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 41 publications
8
56
0
Order By: Relevance
“…The extraordinary ability (separation factor value, α, equal to 2.69) exihibited by the glycopeptide‐type chiral selector (SO) in discriminating the two carnosine enantiomers (the selectand, SA) [4], stimulated us to gain more insight into the molecular basis governing the underlying stereorecognition mechanism. A multitude of computational approaches, including docking and molecular dynamic simulations together with descriptive methods, have been so far applied to facilitate the comprehension of the intricate multifactorial process materializing in enantioselective analysis settings [6–10].…”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary ability (separation factor value, α, equal to 2.69) exihibited by the glycopeptide‐type chiral selector (SO) in discriminating the two carnosine enantiomers (the selectand, SA) [4], stimulated us to gain more insight into the molecular basis governing the underlying stereorecognition mechanism. A multitude of computational approaches, including docking and molecular dynamic simulations together with descriptive methods, have been so far applied to facilitate the comprehension of the intricate multifactorial process materializing in enantioselective analysis settings [6–10].…”
Section: Introductionmentioning
confidence: 99%
“…For the chloro‐substituted CSPs (Chiralpak IC and Chiralpak ID), the presence of chlorine atoms on the phenyl ring may be the reason for their higher enantioselectivity abilities. The chlorine atom was reported to have a double role : (a) the stereoelectronic properties of the chlorine (electron‐withdrawing inductive effect) can influence close sites. In detail, the chloro‐substituted phenyl ring was π‐acidic, and could promote π‐π interaction with π‐basic phenyl ring of the enantiomer, further leading to a better chiral recognition.…”
Section: Resultsmentioning
confidence: 99%
“…In the last years, our groups investigated the factors governing HPLC enantioseparation of atropisomeric halogenated 4,4’‐bipyridines on polysaccharide‐based CSPs . Following these studies, we have demonstrated the contribution of XB and chalcogen bonds (ChBs) for the enantiorecognition of analytes on CDMPC under NP elution conditions.…”
Section: Molecular Dynamics Simulations Of σ‐Hole‐driven Enantioseparmentioning
confidence: 99%
“…On this basis, we used the ESH concept to model XB in CDMPC‐ and ADMPC‐halobipyridine complexes by MD simulations (10 ns of simulation time) (Fig. ).…”
Section: Molecular Dynamics Simulations Of σ‐Hole‐driven Enantioseparmentioning
confidence: 99%
See 1 more Smart Citation